Therapeutic effect of combination of Nigella sativa, Melissa officinalis extract and fennel fruit with citalopram on menopausal symptoms - Gholamreza Amin (Tehran University Medical Journal, 2018)
Background: Menopause is a critical and sensitive period and has a common symptom of vasomotor signs, psychologic changes and sleep disorders. With regarding the citalopram complications and effects of Iranian herbs, the aim of this study was to compared the therapeutic effect of the combination of area part of Melissa officinalis and fennel fruits extract with Nigella sativa powder with citalopram on menopausal symptoms of post-menopausal women. Methods: This randomized clinical trial was conducted in Islamic Azad University of Pharmaceutical Sciences, Tehran, Iran, from April 2015 to October 2017. 56 postmenopausal women referred to the clinics of Gorgan health centers with the age between 45 and 65 years, natural menopause confirmed by amenorrhea for at least 12 months, discomfort a hot flash were randomized to two treatment groups. Group 1 (28 patients) received 1000 mg (Melissa officinalis extract, Nigella saliva powder, and fennel fruits) and Group 2 (19 subjects) received 20 mg citalopram in an eight-week course of treatment (1 per day for each group). The frequency of the variables in the Menopause-Specific Quality of Life Questionnaire (MENQOL) was compared in the two groups before and post intervention. The questionnaire included of twenty-nine questions in four domains of vasomotor, psycho-social, physical and sexual symptoms. Results: The mean age in the herbal treatment group was 47.78±5.5 years and in the citalopram group was 46.4±4.9 years, and t-test did not show this difference in two groups (P=0.362). There was no significant difference in the improvement of menopausal symptoms compared to the citalopram group in the combined product group, but the feeling of anger and fatigue in the citalopram group was greater after treatment (P=0.03). Conclusion: The present study showed that the combination of Nigella Sativa, Melissa officinalis extract, and fennel fruits generally do not reduce menopausal symptoms in postmenopausal women, and it's just the feeling of anger and fatigue has been better than the citalopram group.